PERAN NAA, GA3, KARBON AKTIF, DAN SUKROSA DALAM KULTUR EMBRIO ZIGOTIK KLON OG HYBRID (Elaeis guineensis JACQ. X Elaeis oleifera) OPEN POLLINATED - Ernayunita Ernayunita; Hernawan Yuli Rahmadi; Iman Yani Harahap; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2016)
Oil palm OG hybrid genetic potentials are high in term of vegetative and generative traits, such as: low height increment, compact palm, high free fatty acid and high carotenes. However, OG hybrid reproduction is hindered due to its low germination rate. So, alternative method for germination is needed, which is in vitro embryo zygotic culture. This study objective was to reveal the best medium composition for OG hybrid embryo culture by modificated several oil palm basic medium from oil palm tissue culture protocol and to understand the role of plant growth regulators, activated charcoal, and sucrose on in vitro growth and development of OG hybrid embryo. The design used was Completely Randomized Design (CRD) with 16 replication and 4 embryos for each replicates, while the treatments were: A1 = M129 (control); A2 = M129 + activated charcoal; A3 = M129+ activated charcoal + sucrose; A4 = ½ M129 + activated charcoal + sucrose; A5 = M129 + GA3 ; and A6 = M129 + GA3 + NAA. From the study we found that the best medium for OG hybrid open pollinated clone's embryo culture was M129 with GA3 and NAA (A6). This medium gave percentage of in vitro germination up to 14.06%, and later on the plantlets from this medium gave the best vegetative growth performance such as high number of leaves and primer roots.